Exploration of Theoretical Foundation of Mindfulness-Based Cognitive Therapy: With Special Reference to the Satipaṭṭhāna Sutta - Nikapitiya, Nandarathana; Jay Kumar Ranjan (Journal of International Buddhist Studies, 2024)
The present research investigates the theoretical foundations of mindfulness-based cognitive therapy (MBCT), focusing on the Satipaṭṭhāna Sutta, a foundational text in Buddhist meditation practice. The study aims to examine the foundational framework of MBCT by assessing the congruence between MBCT practices and techniques and Buddhist meditation methods explained in the Satipaṭṭhāna Sutta. Even though MBCT is an evidence-based psychotherapeutic intervention for preventing the relapse of depression, its theoretical foundation and mechanism of efficacy remain insufficiently investigated. Through a cross-cultural perspective, this study evaluates the relationship between MBCT and the Satipaṭṭhāna Sutta and its implications for the development of MBCT as a therapeutic intervention, focusing on the connections between the theoretical underpinnings of MBCT and the Satipaṭṭhāna Sutta. The findings support that MBCT is an evidence-based intervention that was integrated with ancient knowledge from Asia on the management of depression.